DESIGN AND MANUFACTURE OF A MECHANICAL AGITATOR TO PREPARE CHALLENGE WATER UNDER ANMAT REGULATIONS (Journal of Industrial and Mechanical Engineering, 2024)
This work shows the development of a three-bladed propeller, based on a fluid agitator with an Axial type design; used for low viscosity fluids (
Keywords: Challenge waters; Propeller; 3D print